The scattered disc of HR 8799. Issue 1 (26th November 2018) - Geiler, Fabian; Krivov, Alexander V; Booth, Mark; Löhne, Torsten
Abstract: HR 8799 is a young F0-type star with four directly imaged giant planets and two debris belts, one located exterior and another one interior to the region occupied by the planetary orbits. Not only having an architecture similar to that of our Solar system but also revealing dissimilarities such as high masses of planets, a huge radial extent, and a high mass of the outer debris belt, HR 8799 is considered to be a benchmark to test formation and evolution models of planetary systems. Here, we focus on the outer debris ring and its relation to the planets. We demonstrate that the models of the outer disc, proposed previously to reproduce Herschel observations, are inconsistent with the ALMA data, and vice versa. In an attempt to find a physically motivated model that would agree with both observational sets, we perform collisional simulations. We show that a narrow planetesimal belt and a radiation pressure induced dust halo cannot account for the observed radial brightness profiles. A single, wide planetesimal disc does not reproduce the data either. Instead, we propose a two-population model, comprising a Kuiper-Belt-like structure of a low-eccentricity planetesimal population ('the classical Kuiper Belt') and a high-eccentricity population of comets ('scattered disc'). We argue that such a structure of the exo-Kuiper Belt of HR 8799 could be explained with planet migration scenarios analogous to those proposed for the Kuiper Belt of the Solar system.